2022
DOI: 10.3389/fmed.2022.819465
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Hemophagocytic Lymphohistiocytosis and Cytomegalovirus Disease: A Case Based Systemic Review

Abstract: BackgroundHemophagocytic lymphohistiocytosis (HLH) is an immune mediated life-threatening condition. It is driven by an overactivation of the immune system and causes inflammatory tissue damage potentially leading to organ failure and death. Primary HLH is caused by genetic mutations, while secondary HLH is triggered by external factors. Viral infections are a well-known cause of secondary HLH. Cytomegalovirus (CMV) is a virus in the herpes family known to cause HLH in rare cases.MethodsWe report a recent case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…In patients with CMV-induced HLH, precipitating upper respiratory symptoms such as non-productive cough and malaise can be mild or even absent, followed by persistent fevers, cytopenias, and elevated serum ferritin with or without high serum triglyceride or low fibrinogen 19. Lymphadenopathy and splenomegaly can be absent in around 35% of patients 20. Positive viral serologies with IgG and IgM and positive CMV-DNA PCR (generally greater than 10 000 copies/mL) indicating active infection are usually seen 20–22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with CMV-induced HLH, precipitating upper respiratory symptoms such as non-productive cough and malaise can be mild or even absent, followed by persistent fevers, cytopenias, and elevated serum ferritin with or without high serum triglyceride or low fibrinogen 19. Lymphadenopathy and splenomegaly can be absent in around 35% of patients 20. Positive viral serologies with IgG and IgM and positive CMV-DNA PCR (generally greater than 10 000 copies/mL) indicating active infection are usually seen 20–22.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphadenopathy and splenomegaly can be absent in around 35% of patients 20. Positive viral serologies with IgG and IgM and positive CMV-DNA PCR (generally greater than 10 000 copies/mL) indicating active infection are usually seen 20–22. In CMV-induced HLH, most patients receive both antiviral and immunosuppressive therapies (usually high-dose steroids such as dexamethasone), with or without the chemotherapy etoposide, with an expected response in usually 3–10 days 17 19 23.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we are focusing on virus-associated haemophagocytic syndrome (VAHS). Recent research has shown that several types of viruses, including EBV [32,33], CMV [34], HIV [35], parainfluenza virus [36], human herpesvirus Type 6 (HHV-6) [37] and other types of viruses [38] can trigger HLH. Among VAHS, EBV is major cause of HLH, and EBV-HLH is associated with a high risk of death and multi-organ failure.…”
Section: Virus-associated Haemophagocytic Syndromementioning
confidence: 99%
“…Primary, or familial HLH, is caused by inherited genetic mutations that disrupt the function of cytotoxic T cells and natural killer (NK) cells [ 2 ]. Symptoms are often severe and present early in life [ 3 ]. Secondary or acquired HLH is induced by a variety of triggers including infection, malignancy, autoimmunity, and immunosuppression [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%